Village Fund Accounting Treatment And Accountability Reporting in Noemuke Village - Selan, Ongki Arwadi; Susilawati , Made; Atto , Aplonia (GOVERNORS, 2025)
The aim of this research is to determine the accounting treatment of village funds and accountability reports in Noemuke Village. Data collection techniques use interview data. The research results show that the Head of Noemuke Village is transparent in accounting for village funds and accountability reports. This is because the Noemuke village head is open to the community regarding financial reports and village fund accountability reports. The village head also provides information related to the final report on the use of village finances so that the community knows about the final use of existing budget funds. The accounting treatment and accountability reporting of village funds in Noemuke Village generally follow applicable regulations, using the Siskeudes application in line with Permendagri No. 20 of 2018. The financial management cycle—from planning to accountability—is implemented, though challenges remain in human resource capacity, technical assistance, and timely reporting. Community empowerment receives the largest budget allocation, reflecting development priorities. While accountability reports are formally prepared and submitted, transparency to the community is limited, and audits focus mainly on administration. Overall, implementation is fairly good but needs improvement in transparency, timeliness, and public involvement to strengthen governance.